A learned society against mafias (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
This contribution focuses on the role that SISMA, the learned society on mafias and anti-mafias, can play in the academic context. Three expected functions are emphasised: enhancing the interdisciplinary and potentially transdisciplinary matrix of research; deepening conceptual analysis as a prerequisite for grasping causal links with contiguous phenomena; the necessary link with anti-mafia policies, as the potential core for the creation of an epistemic community.
Keywords: mafia; anti-mafia; learned society; transdisciplinarity; epistemic community